How β-cyclodextrin- loaded mesoporous SiO2 nanospheres ensure efficient adsorption of rifampicin - Sun, Xun; Chen, Mingming; Lei, Jiayu; Liu, Xinran; Ke, Xin; Liu, Wengang; Wang, Jingkuan; Gao, Xiaodan; Liu, Xin; Zhang, Yun (Frontiers in Chemistry, 2022)
In this study, β-CD@mesoporous SiO2 nanospheres (β-CD@mSi) were prepared by loading β-cyclodextrin (β-CD) onto mesoporous silica nanospheres through an in situ synthesis. This not only solved the defect of β-CD being easily soluble in water, but also changed the physical structure of the mesoporous silica nanospheres. FTIR and XPS results showed that β-CD was successfully loaded onto mesoporous silica nanospheres (mSi), while enhancing the adsorption effect. β-CD@mSi with a monomer diameter of about 150 nm were prepared. At a temperature of 298k, the removal efficiency of a 100 mg/L solution of rifampicin can reach 90% in 4 h and the adsorption capacity was 275.42 mg g−1 at high concentration. Through the calculation and analysis of adsorption kinetics, adsorption isotherms and adsorption thermodynamics based on the experimental data, the reaction is a spontaneous endothermic reaction dominated by chemical adsorption. The electron transfer pathway, structure–activity relationship and energy between β-CD@mSi and rifampicin were investigated by quantum chemical calculations. The accuracy of the characterization test results to judge the adsorption mechanism was verified, to show the process of rifampicin removal by β-CD@mSi more clearly and convincingly. The simulation results show that π–π interaction plays a major interaction in the reaction process, followed by intermolecular hydrogen bonding and electrostatic interactions.